English Language Lecturers’ Perception About Learner Autonomy - Tesa Yoshika Puteri; Loli Safitri (Universitas Pahlawan Tuanku Tambusai, 2021)
The English language lecturers’ perception about learner autonomy is important in order to help their learners develop their learning autonomy in the classroom. The purpose of this research was to know what was the English Language Lecturers’ Perception about Learner Autonomy. The descriptive quantitative research has the English lecturers of IAIN Bukittinggi as subject of the research. There were 11 English lecturers that used as the sample in this research. The instrumentation in this research was questionnaire. In analyzing the data, the researcher used the percentage formula. The research findings showed that most of the English lecturers were “unsure”. Data analysis was proven that there were 69 (34.84%) the total responses from the English lecturers that stated “unsure (U)” in the questionnaires about learner autonomy. In conclusion, most of the English lecturers were “unsure” about the learner autonomy.